Hibridismos regulatórios: uma análise do processo de agencificação no saneamento básico brasileiro - Souza, Celso Florêncio de (2013)
The aim of the present study is to understand how c ontextual factors have affected the transfer of independent regulatory agencies (IRAs) in Brazil ian water and sanitation sector. The divergence in transfer process has led hybrids mode ls of IRAs in this sector. Thus, the empirical contribution of this study is: (i) to demonstrate the main factors involved in the transfer, and (ii) to identify different types of ARIs resulted from water and sanitation context. These models are: (i) Multisectoral state IRAs, (ii) State ARI (exclusive for water and sanitation), (iii) municipal ARIs, (iv) Regional ARIs and (v) Buro/regulocracy. However, to identify the factors and to understand the resulted ARIs, it was necessary create a theoretical model to overcome policy transfer literature’s rest rictions. Therefore, we combined the policy transfer theory with path dependence literature, be cause our first analyses showed the importance of water and sanitation sector’s dynamic in the IRAs transfers. Thus, overcoming one of the main limitations of the policy transfer framework – a 'one way' transfer direction - is the main theoretical contribution of this study.